Nanotechnology in Orthodontics: Unveiling Pain Mechanisms, Innovations, and Future Prospects of Nanomaterials in Drug Delivery - Sharma, Divya; Kumar, Shiv; Garg, Yogesh; Chopra, Shruti; Bhatia, Amit (Current Pharmaceutical Design, 2024)
Orthodontic pain is characterized by sensations of tingling, tooth discomfort, and intolerance. According to the oral health report, over forty percent of children and adolescents have undergone orthodontic treatment. The efficacy of orthodontic treatment involving braces can be compromised by the diverse levels of discomfort and suffering experienced by patients, leading to suboptimal treatment outcomes and reduced patient adherence. Nanotechnology has entered all areas of science and technology. This review provides an overview of nanoscience, its application in orthodontics, the underlying processes of orthodontic pain, effective treatment options, and a summary of recent research in Nano-dentistry. The uses of this technology in healthcare span a wide range, including enhanced diagnostics, biosensors, and targeted drug delivery. The reason for this is that nanomaterials possess distinct qualities that depend on their size, which can greatly enhance human well-being and contribute to better health when effectively utilized. The field of dentistry has also experienced significant advancements, particularly in the past decade, especially in the utilization of nanomaterials and technology. Over time, there has been an increase in the availability of dental nanomaterials, and a diverse array of these materials have been extensively studied for both commercial and therapeutic purposes.
Keywords: orthodontic pain